PENGARUH PEMBERIAN PROBIOTIK YANG DICAMPUR PAKAN DENGAN DOSIS BERBEDA TERHADAP PERTUMBUHAN DAN SINTASAN IKAN NILA SALIN (Oreochromis aureus x niloticus) - Baedlowi Baedlowi; Aminin Aminin (Universitas Muhammadiyah Gresik, 2021)
Saline tilapia (Oreochromis aureus x niloticus) is a superior strain that was released by the Indonesian Ministry of Marine Affairs and Fisheries in 2012. The advantages of saline tilapia are tolerance to high environmental temperatures and high immunity against disease attacks. The feed has an important role in the growth of tilapia and requires 60-70% of the production cost. However, the high price of feed can increase production costs and require cultivators to be more careful and have a good strategy in cultivation. One of the efforts to reduce the cost of feed is the application of probiotics with the right dose. The method used in this study is an experimental method using a completely randomized design (CRD) consisting of 3 treatments and 1 control which was classified into; treatment K (without probiotics), Treatment A (5 ml/kg of feed), Treatment B (10 ml/kg of feed), Treatment C (15 ml/kg of feed). The research was carried out for 28 days, with the conclusion that the best results were obtained by treatment A (5 ml/kg of feed) with an absolute length of 3.28 cm, an absolute weight of 5.87 grams, SGR 0.21% /day, and SR 90%.